The Swiss Sovereign Money Initiative - Katrin Assenmacher; Claus Brand (Credit and Capital Markets – Kredit und Kapital, 2018)
On 10 June 2018, Switzerland voted against a constitutional amendment to introduce a system of sovereign money or Vollgeld. The proposal foresaw that all money be created by the central bank and that commercial banks be banned from creating demand deposits. Demand deposits would have been required to be held in off-balance sheet accounts at commercial banks. We discuss the specific features of this proposal and compare them to its historical predecessor, the Chicago plan. We argue that the Swiss initiative would not have tangibly enhanced financial, monetary, and economic stability. Specifically, if implemented earlier, it would not have addressed the root causes of the Global Financial Crisis and would have been ineffective in changing its course and its consequences for Switzerland. Though the Vollgeld proposal would have turned commercial bank into central bank money, close-money substitutes would likely have remained on the liability side of commercial bank balance sheets. Vollgeld would also unlikely have redeemed promises of ancillary effects such as a reduction in public debt, more sustainable economic growth, and less complex regulation. Forestalling and tackling financial imbalances requires limiting leverage and safeguarding liquidity buffers through bank-level and system-wide rules and regulation. – – Am 10. Juni 2018 lehnten drei Viertel der Schweizer Stimmberechtigten eine Verfassungsänderung ab, die ein Vollgeldsystem in der Schweiz eingeführt hätte. Der Vorschlag hätte der Notenbank das alleinige Recht zur Geldschöpfung gegeben und den Geschäftsbanken die Schaffung von Sichteinlagen verboten. Zahlungsverkehrskonten hätten von den Geschäftsbanken ausserhalb ihrer Bilanz geführt werden müssen. Wir diskutieren die Einzelheiten des Vorschlags und vergleichen sie mit dessen Vorgänger aus den 1930er Jahren, dem Chicago Plan. Wir argumentieren, dass sich die monetäre und wirtschaftliche Stabilität sowie die Finanzstabilität in der Schweiz durch die Annahme der Initiative nicht wesentlich verbessert hätten. Ein bestehendes Vollgeldsystem hätte nicht bei den Ursachen der Finanzkrise angesetzt und wäre unerheblich für ihren Verlauf und ihre Folgen für die Schweiz gewesen. Obwohl mit Vollgeld Sichteinlagen bei Geschäftsbanken in Zentralbankgeld umgewandelt worden wären, hätten geldnahe Einlagen auf der Passivseite der Bilanz weiter existiert. Vollgeld hätte auch Versprechen wie eine Senkung der Staatsverschuldung, ein nachhaltigeres Wachstum und eine weniger komplexe Bankenregulierung nicht erfüllt. Die Verhinderung und Bewältigung von finanziellen Ungleichgewichten erfordert eine Regulierung sowohl auf Bankenebene als auch für das Finanzsystem insgesamt, um die gesamtwirtschaftliche Verschuldung zu beschränken und Liquiditätspuffer zu schaffen.
Keywords: E42; E50; 330; Sovereign money; Chicago plan; money supply; reserves; financial stability